A comparison of nursing tasks undertaken by regulated nurses and nursing support workers: a work sampling study. (22nd December 2016) - Roche, Michael A.; Friedman, Sarah; Duffield, Christine; Twigg, Diane E.; Cook, Rebecca
Abstract: Aims: The aim of this study was to determine which tasks unregulated nursing support staff spend their work time undertaking and to determine differences between the work undertaken by licensed/regulated nurses on units which have nursing support workers and those on units which do not. Background: Acute hospital nursing teams often include nursing support staff; little is known about what kinds of tasks these unregulated support workers do and how it affects the work tasks of their licensed/regulated team members. Design: Cross‐sectional analysis of nurse work sampling data. Methods: Data collection took place between March–October 2013. The proportion of time spent on 25 work activities by nursing support staff and licensed/regulated nursing staff was compared. Logistic regression models estimated whether nursing support staff or licensed/regulated nurses were more likely to conduct direct and indirect patient care tasks and whether licensed/regulated nurses on units with nursing support staff were more likely to conduct direct or indirect tasks compared with those on units without nursing support workers. Results: Nursing support staff spent the majority of their time engaged in direct care tasks, e.g. admission and assessment, hygiene and mobility. Although licensed/regulated nurses were less likely to undertake direct care tasks compared with support workers, those who worked on units with support workers undertook more direct care compared with those who worked on units without support workers. Conclusions: Nursing support workers were given tasks that required substantial amounts of patient interaction. These staff may be associated with an increase in direct care tasks for licensed/regulated nurses, who may duplicate the direct care done by nursing support workers.